Unsteady Dungey cycle from the point of view of Stokes’ theorem - Semenov, Vladimir S.; Kubyshkin, Igor V.; Tsyganenko, Nikolai A.; Erkaev, Nikolai V.; Kubyshkina, Marina V.; Wang, Xiaogang (Frontiers in Astronomy and Space Sciences, 2024)
The Dungey cycle is considered from the formation of a magnetic barrier and necessary for dayside reconnection conditions till the electric field generation around the Birkeland current loop and magnetic flux circulation balance. Data-based modeling of the magnetosheath magnetic field makes it possible to quantitatively assess the main factors that control formation and destruction of the magnetospheric magnetic barrier, such as the field line draping and the field intensity increase from the bow shock to the magnetopause, as well as their dependence on the orientation of the interplanetary magnetic field (IMF). The Dungey cycle has been revised to take into account the essentially time-dependent effects of magnetic reconnection. It is shown by means of the Stokes’ theorem that a powerful electric field with an effective potential difference of several tens of kV is generated around the developing substorm current system. The emerging Birkeland current loop is an important particle acceleration element in the magnetosphere, contributing to the energization of ring current protons and electrons. The electric field that arises in the dipolarization zone magnifies the already existing ring current, and the closure of its amplified part through the ionosphere generates the Region 2 field-aligned currents. The motion of the expanding partial ring current around the magnetosphere, combined with the particle drift, transfers the magnetic flux from the night side of the magnetosphere to the dayside. At the dayside magnetopause, the reconnection is also responsible for the creation of the Birkeland loop, but now the electric field in the loop area decelerates the ring current particles, and regions of weakened ring current are formed. Closure of these weakened loop currents results in a transfer of the magnetic flux from the dayside to the night side, thus ensuring its overall balance and completing the Dungey cycle.